Reliability and validity of modified upper limb neurodynamic tests in patients with cervical radiculopathy - Rupa Zanwar; Surendra Wani (Hong Kong Physiotherapy Journal, 2024)
Background: Neurodynamic Tests (NDTs) are used to assess neural mechanosensitivity in various conditions such as neural sliding, tension or inflammatory dysfunction. But in some upper quadrant dysfunctions, standard testing procedure of NDT cannot be assessed or tolerated by patient. Objective: The purpose of the study was to determine the validity, intra-rater and inter-rater reliability of modified NDTs via median and ulnar nerve in patients with cervical radiculopathy. Methods: Thirty-three patients (18 men and 15 women, mean age ± SD [Formula: see text]) with cervical radiculopathy having positive response to standard NDTs were included in the study. Modified neurodynamic tests for median & ulnar nerve were performed with modification in the sequencing of standard neurodynamic test at lower degrees of glenohumeral abduction and external rotation. Outcome measures used were angle of elbow extension for median nerve and angle elbow flexion for ulnar nerve at the point of pain onset indicated by “OP” (Onset of Pain). Results: Reliability of OP was evaluated using measurement of Intra-class Correlation Coefficient (ICC), Standard Error of Measurement (SEM) and Minimal Detectable Change (MDC) values. Results indicated high ICC values and low SEM values for OP during modified median and modified ulnar NDTs (M-MNT1 and M-UNT) on symptomatic side of patients with cervical radiculopathy. Spearman correlation analysis for validity of test score showed strong correlation ([Formula: see text]) with standard NDT. Conclusion: There was strong correlation between Modified NDTs and standard tests depicting good validity and substantial reliability of OP during M-MNT1 and M-UNT for positive NDT response in patients with cervical radiculopathy.